Happiness and productivity in the construction sector: a systematic literature review on the influential factors - Mohammad Waffy, Fazil; Mohd Hanafiah, Ahmad; Md Asrul Nasid, Masrom; Lee, Chia Kuang (Springer Nature Singapore, 2026)
The acknowledged correlation between happiness and productivity in the construction industry highlights a critical research gap. This study aims to address this gap by comprehensively identifying global determinants of happiness and elucidating factors that moderate and mediate the happiness-productivity relationship within the construction sector. This systematic literature review explores the primary factors contributing to individual happiness and examines the prevailing trends in research concerning the relationship between happiness and productivity. While this methodological choice aimed to ensure research quality, it may have limited the breadth of our findings. Our investigation categorizes happiness factors into five main groups: personal, job-related, social, leadership, and environmental factors. Additionally, this study identifies several moderators and mediators that influence the relationship between happiness and productivity such as personal factors, job-related factors, and leadership. Moving forward, future research regarding this research area should adopt a more comprehensive approach, encompassing a broader spectrum of factors that influence happiness and its consequent impact on productivity across various contexts. This broader perspective holds the potential to enrich the depth and applicability of our insights.